Bibliometric evaluation of publications on inflammasomes in atherosclerosis from 2002 to 2022 - Tan, Yu; Yu, Yanqiao; Liu, Wei; Ma, Xiaojuan; Shi, Dazhuo (Frontiers in Cardiovascular Medicine, 2023)
Background Inflammasomes have emerged as an important and promising area of investigation in atherosclerosis. This field, however, lacks bibliometric studies. To help understand how basic and clinical research on inflammasomes in atherosclerosis will develop in the future, we used bibliometric analysis to visualize hotspots and trends. Methods Studies related to inflammasomes in atherosclerosis were collected from the Web of Science Core Collection database. Each study was analyzed bibliometrically and visually. CiteSpace and VOSviewer software were used to generate knowledge maps. Results A total of 894 articles were identified. Sixty-two countries and 338 institutions led by China and the United States contributed to these publications. The leading research institutions were Harvard Medical School and Columbia University. Circulation was the most frequently cited journal in this field. Among the 475 authors determined, Eicke Latz authored the most studies, and Peter Duewell has been cocited the most. NLRP3 inflammasome, NF-kappa B, macrophage and oxidative stress are the most commonly used keywords. Conclusion There has been a blooming of research on inflammasomes in atherosclerosis during the last two decades. Future studies will likely explore the molecular mechanism of inflammasomes in cell death. More compellingly, researchers may further delve into the potential clinical value of affecting pathological changes in atherosclerosis by modulating the initial transcription immune response and intracellular multiprotein assembly process of the NLRP3 inflammasome. Our research will be helpful to scholars focusing on inflammation—a much-needed breakthrough in the pathophysiological alterations of atherosclerosis—with a novel perspective.